Is quality still free?: Empirical evidence on quality cost in modern manufacturing - Plewa, Markus; Kaiser, Gernot; Hartmann, Evi (International Journal of Quality and Reliability Management, 2016)
Purpose The purpose of this paper is to provide empirical evidence for competing representations of the prevention-appraisal-failure model of quality cost. Design/methodology/approach The authors conduct regression analysis on a secondary data set to reveal relationships among total cost of quality, its components and overall quality performance. Findings Total cost of quality and its failure cost component are significantly lower at higher levels of quality, while the prevention and appraisal cost components are not observed to be significantly higher at higher levels of quality. The authors propose a modification to the modern representation of the prevention-appraisal-failure model. Practical implications In manufacturing, ever higher levels of quality are associated with significantly lower quality cost. Originality/value Using a large, unique data set for secondary analysis, combined with employing a high-level measure for overall quality performance, the authors provide evidence for the aggregate explanatory power of prevalent representations of the prevention-appraisal-failure cost of quality mode
Keywords: Manufacturing; Quality management; Quality costs; Secondary data analysis